PERTUMBUHAN TANAMAN AGROFORESTRI DAN KONDISI TAPAK DI AREAL REVEGETASI DI KAWASAN HUTAN LINDUNG LIANG ANGGANG BANJARBARU - Risna Hardiyanti; Hamdani Fauzi; Eko Rini Indrayatie (Jurnal Sylva Scienteae, 2021)
This study aims to analyze the growth of agroforestry plants and soil fertility at site conditions in the revegetation area of the Protected Forest Area Liang Anggang Banjarbaru. This research was conducted in the Liang Anggang Protected Forest Area, for 3 months. To analyze plant growth data and analysis of soil fertility using two methods, namely the analysis of plant growth using the method of determining the percentage of plant growth, while the analysis of soil fertility in site conditions based on physical and chemical of soil characteristics. The results showed that in the research location there were 9 types of plants, namely Petai, Belangiran, Mango, Longan, Rambutan, Soursop, Sawo, Jengkol and Citrus plants with a total plant of 377 individuals. There were 214 individuals at location 1 and there were 163 individuals at location 2. The highest percentage of plant life was petai at 63.69% and the lowest percentage was soursop plants at 6.25%. The highest plant height was jengkol at 177.83 cm, while the lowest was longan plant at 58.62 cm. The highest plant diameter was petai plants with a diameter of 2.1 cm while the lowest was longan plants with a diameter of only 1.0 cm. Soil fertility in the research site, the soil type has low fertility. The low fertility at the research location is due to limiting factors, namely the low content of P2O5, K2O and saturation of soil alkalisPenelitian ini bertujuan untuk menganalisis pertumbuhan tanaman agroforestri dan kesuburan tanah pada kondisi tapak di areal revegetasi di Kawasan Hutan Lindung Liang Anggang. Penelitian ini dilaksanakan di Kawasan Hutan Lindung Liang Anggang, Selama 3 bulan. Untuk menganalisis data pertumbuhan tanaman dan analisis kesuburan tanah menggunakan dua metode yaitu analisis pertumbuhan tanaman menggunakan metode penentuan persentase tumbuh tanaman sedangkan analisis kesuburan tanah pada kondisi tapak dengan menggunakan uji sifat fisik dan kimia tanah. Hasil penelitian diketahui bahwa dilokasi penelitian terdapat 9 jenis tanaman yaitu tanaman Petai, Belangiran, Mangga, Kelengkeng, Rambutan, Sirsak, Sawo, Jengkol dan Jeruk dengan total tanaman sebanyak 377 individu. Ada sebanyak 214 individu pada lokasi 1 dan terdapat 163 individu pada lokasi 2. Persentase hidup tanaman yang tertinggi ialah petai sebesar 63,69% dan persentase yang terendah ialah tanaman Sirsak sebesar 6,25%. Tinggi tanaman yang tertinggi ialah tanaman jengkol sebesar 177,83 cm sedangkan yang terendah ialah tanaman kelengkeng sebesar 58,62 cm. Diameter tanaman yang tertinggi ialah tanaman petai dengan diameter 2,1 cm sedangkan yang terendah ialah tanaman kelengkeng dengan diameter hanya 1,0 cm. Kesuburan tanah pada tapak penelitian, jenis tanahnya memiliki kesuburan rendah. Faktor pembatas yang menyebabkan rendahnya kesuburan pada lokasi penelitian, rendahnya kandungan P2O5, K2O dan kejenuhan basa tanah